Study of ossicular chain defects in patients with chronic otitis media - Soni, Smita; A. R., Anjali; J. K., Yashveer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media (COM) is a long-standing disease of middle ear cleft and mastoid cavity having a permanent perforation in the tympanic membrane with or without discharge. It’s a worldwide health problem and it is still predominant in the modern antibiotic era. Aim was to determine the prevalence and types of ossicular chain defect in mucosal and squamosal type of COM. Also, to evaluate the hearing loss in relation to ossicular chain defect. Methods: The study was prospective observational study conducted in Bhopal over the duration of one year (January 2019 to June 2020). Patient aged 11-70 years reporting with COM were included in the study. Details regarding sociodemographic profile and extensive examination were recorded. Data was entered into MS excel 2007, analysis was done. Results: It was more prevalent in the age groups of 21-30years (39%) with female (53%) preponderance. Right sided ear was commonly involved (58%). Majority of the patients had tubo-tympanic disease (62%) whereas 38% had attico-antral disease. Ossicular chain was found intact in 33% cases. Average hearing loss was maximum (67.6 dBHL) when all ossicles are eroded. Hearing loss was minimum (33.6 dBHL) with isolated handle of malleus involvement. Conclusions: COM is one of the commonest causes of preventable hearing impairment in our society, hence early diagnosis and timely intervention is needed. Awareness among patients and doctors regarding the need for better ear hygiene is necessary.